Government Spending, Corruption and Output Growth in Nigeria - Olarewaju F., Ogunlana (European Scientific Journal, ESJ, 2016)
This study used the works of Barro(1990), Bakare(2011), and Dissou and Yakautsava (2011) to establish the relationship between government spending, corruption and output growth in Nigeria. It employed aggregated data from 1980 to 2011. Using the Johansen Maximum Likelihood procedure and error correction mechanism, the study showed that the estimates of money supply, capital formation, openness to trade and innovation system positively influenced output growth while unemployment and domestic debt affected output negatively. Public investment as a percentage of GDP and corruption influenced adversely output growth. The paper recommends that corruption tilts public spending away from growth enhancing projects and towards low and less productive ones.